75.2k views
2 votes
2x
2x^(2)-3x-5

User TheoF
by
4.9k points

2 Answers

3 votes

Answer:

(x + 1)(2x - 5)

Explanation:

Assuming you require the expression factorised.

2x² - 3x - 5

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 2 × - 5 = - 10 and sum = - 3

The factors are + 2 and - 5

Use these factors to split the x- term

2x² + 2x - 5x - 5 ( factor the first/second and third/fourth terms )

= 2x(x + 1) - 5(x + 1) ← factor out (x + 1) from each term

= (x + 1)(2x - 5) ← in factored form

User Eray
by
5.0k points
2 votes

Answer:

2x²-3x-5

=2x²-3x-5

=2x²-5x+2x-5

=2x(x-5)+2(x-5)

=(x-5)(2x+2)

User ABH
by
5.2k points